(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
One of the primary objectives of this paper is to assess the level of job satisfaction among college faculty members. The findings reveal a notable distribution of satisfaction levels: 30 percent of the respondents reported being 'not satisfied' with their jobs, 58 percent indicated they were 'moderately satisfied,' and 11 percent expressed being 'highly satisfied.' This indicates that the majority of the college faculty members fall into the 'moderately satisfied' category. Furthermore, the study uncovered significant variations in job satisfaction across different categories of colleges, highlighting that job satisfaction levels are not uniform and differ depending on the type of institution.